CHALLENGES AND SPECIFICITY OF ENSURING THE ECONOMIC SECURITY OF THE ENTERPRISE IN CRISIS CONDITIONS - Анна Жураковська; Дар’я Лукашова; Роман Павлов (Економіка та суспільство)
The article focuses on the study of current challenges and peculiarities of ensuring economic security of enterprises in times of crisis. Different approaches to understanding the concept of economic security and its components are analyzed. It is determined that the key element is financial security, which requires special attention in the context of martial law. The influence of external threats on the activities of enterprises is investigated and the basic principles of financial security management are systematized. Innovative approaches to the transformation of business processes, including digitalization, data management and supply chain optimization, are considered. The main components of the financial security mechanism are highlighted: information and organizational, functional and analytical, control and monitoring.